Phosphorylation of the transcriptional repressor MYB15 by mitogen-activated protein kinase 6 is required for freezing tolerance in Arabidopsis. Issue 11 (16th May 2017) - Kim, Sun Ho; Kim, Ho Soo; Bahk, Sunghwa; An, Jonguk; Yoo, Yeji; Kim, Jae-Yean; Chung, Woo Sik
Abstract: The expression of CBF (C-repeat-binding factor) genes is required for freezing tolerance in Arabidopsis thaliana. CBFs are positively regulated by INDUCER OF CBF EXPRESSION1 (ICE1) and negatively regulated by MYB15. These transcription factors directly interact with specific elements in the CBF promoters. Mitogen-activated protein kinase (MAPK/MPK) cascades function upstream to regulate CBFs . However, the mechanism by which MPKs control CBF expression during cold stress signaling remains unknown. This study showed that the activity of MYB15, a transcriptional repressor of cold signaling, is regulated by MPK6-mediated phosphorylation. MYB15 specifically interacts with MPK6, and MPK6 phosphorylates MYB15 on Ser168. MPK6-induced phosphorylation reduced the affinity of MYB15 binding to the CBF3 promoter and mutation of its phosphorylation site (MYB15 S168A ) enhanced the transcriptional repression of CBF3 by MYB15. Furthermore, transgenic plants overexpressing MYB15 S168A showed significantly reduced CBF transcript levels in response to cold stress, compared with plants overexpressing MYB15. The MYB15 S168A -overexpressing plants were also more sensitive to freezing than MYB15 -overexpressing plants. These results suggest that MPK6-mediated regulation of MYB15 plays an important role in cold stress signaling in Arabidopsis .